STRUCTURAL COMPARISON OF PROKARYOTIC AND EUKARYOTIC FOLATE TRANSPORTERS BY COMPUTATIONAL APPROACH - Agarwal, Deepa; Jha, Alok (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In silico approach has particularly drawn attention in providing a realistic representation needed to understand the fundamental molecular structure of a transporter. The importance of folate metabolism and role in the internalization of antifolates in eukaryotes have been studied extensively, but the structural study of folate transporters in Homo sapiens (HFT), Plasmodium falciparum (PFT), and Streptococcus sp. (SFT) is still lacking. This study was conducted to study and compare the structures of prokaryotic and eukaryotic folate transporters. Methods: HFT, PFT, and SFT were queried using blast and sequences were retrieved using National Center for Biotechnology and Information (NCBI) databases. This was superseded by structural and functional prediction of transporters. The structure has been generated using Swiss model which was visualized using PyMol and validated by Procheck and ERRAT analysis along with the values of different secondary structures mapping to diverse sections of the Ramachandran plot. The structural and functional comparison was performed by PROSO, ProFunc, TM Score, Porewalker, TMHMM, and Protscale. Result: All the parameters for structural comparison suggest that H. sapiens folate transporter is 16.67% and 17.72% identical to Plasmodium and Streptococcus whereas Plasmodium is 21.59% identical to Streptococcus. The evaluation of transmembrane helices and hydrophobicity resulted in the presence of 1, 4, and 12 membrane-spanning segments with predicted US, UDUD, and UDS as pore shape in Plasmodium, Streptococcus, and humans. Conclusion: Such folate receptors are the main targets for the specific conveyance of antifolates. The differences found between these species may offer possibilities for the development of new drugs in future.Â 